Unpacking wastewater reuse arrangements through a new framework: insights from the analysis of Egypt - Tawfik, Mohamed Hassan; Hoogesteger, J.; Elmahdi, Amgad; Hellegers, Petra J.G.J. (Informa UK Limited, 2021)
Wastewater reuse is identified as strategic to help ameliorate scarcity in water-stressed regions around the world. However, to develop it, there is a need to better understand the social, institutional and technological contexts in which it takes place. This article develops a novel socio-technical framework to inform such an analysis and applies it to current wastewater reuse in Egypt. Our analysis highlights the different actors, management activities and practices that shape wastewater collection, transfer, treatment, discharge and/or reuse in different social, technological and environmental contexts in Egypt. It points out bottlenecks of current wastewater reuse policies and programmes.